Production Of Sugars From Sago Hampas By Trichoderma Sp. During Solid Substrate Fermentation - Shahrim, Zaizuhana (2006)
Advances in industrial biotechnology offer potential opportunities for economic utilization of agro-industrial residues such as sago hampas. Sago hampas, which is a complex material, is one of the major by-product of the sago starch industry. It contains about 69.82% of starch and 13.88% lingo cellulose materials on dry weight basis. Due to its abundant availability, it can serve as an ideal substrate for microbial processes for the production of sugars. Application of solid substrate fermentation technology is an attractive possibility for such bioconversions. In this study, solid substrate fermentation (SSF) of sago hampas by indigenous isolated Trichoderma sp. was carried out. In laboratory scale, SSF was conducted in a 250 mL Erlenmeyer flask contains 5g of hampas was used as solid substrate and 10% (v/w) of mycelia suspension was used as inoculum. Parameters optimised includes the initial moisture content (60, 65, 70, 75 and 80%), mineral salts solution (10, 20 and 30% vlw), urea concentration (0.5, 1.0 and 2.0% wlv), inoculum density (10, 20 and 30% vlw), incubation temperature (25, 30, 35, 40, and 45 "C), incubation time (0, 12, 24, 36, 48, 60, 72, 84, 96, 108 and 120 h) and homogenisation speed (8,000, 9,500 and 13,500 rpm) and time (1, 3 and 5 min) on reducing sugars recovery. Maximum reducing sugars obtained after optimisation was 460 mglg substrate on 96 h incubation with 80% of initial moisture content, 10% (vlw) of inoculum density, 1.0% of urea concentration in 20% (wlv) of mineral salts solution and incubated at 30 + 2 OC. The solid culture was homogenised at 9, 500 rpm for 3 minutes for reducing sugars recovery. Meanwhile, the maximum enzyme activities obtained were 3.19 UImL, 2.22 UImL, 1.66 UImL, 1.1 1 UImL and 1.48 UImL for a-amylase, glucoamylase, carboxymethyl cellulase, filter paperase and Ij-glucosidase respectively. Bioconversion of sago hampas using a rotary drum was conducted by using a modified cement mixer. Operating parameters such as temperature, moisture, agitation and aeration via SSF were studied to achieve higher production of reducing sugar. After 96 h of fermentation, maximum reducing sugar obtained was 380 mglg substrate. Maximum enzyme activities achieved were 2.74 UImL, 2.19 UImL, 1.33 UImL, 1.12 UImL and 1.07 UImL for a-amylase, glucoamylase, carboxymethyl cellulase, filter Paperase and I3-glucosidase, respectively.